Structural Safety Assessment of Existing Multiarch Tunnel: A Case Study - Jinxing Lai; Junling Qiu; Haobo Fan; Jianxun Chen; Zhinan Hu; Qian Zhang; Junbao Wang (Advances in Materials Science and Engineering)
Structural health assessment is one of the key activities in maintaining the performance of a tunnel during its service life. Due to the development of modern detection technology, comprehensive structural health assessment system is being established for operating tunnels. To evaluate the actual operational state of Shitigou tunnel, overall detection of the liner crack, tunnel seepage, and liner void was conducted by employing the modern detection technology, such as crack width monitoring technology, concrete strength monitoring technology, and electromagnetic wave nondestructive monitoring technology. Through the statistical analysis of the detection results, the distribution characteristic, development law, and damage grade of structural defects were obtained. Tunnel liner cracks are mainly located on the middle wall; serious water leakage is encountered on the side wall, middle wall, and vault; the strength of foundation and liner structure of left tunnel does not meet the design requirement; the liner voids are mostly located at the tunnel entrance section, especially, on the tunnel vault; and the proportion of influence factors of structural defects should be considered. The research results presented for this study can serve as references for effective design and health assessment of existing multiarch tunnel projects.